Role of Translation in Global Literary Circulation - Njonge, Eunice (American Journal of Literature Studies, 2024)
Purpose: The aim of the study was to assess the role of translation in global literary circulation. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that translation not only facilitates the accessibility of literary works to a broader audience but also enhances the global understanding and appreciation of diverse literary traditions. Through translation, works of literature from less commonly spoken languages gain international recognition, contributing to cultural diversity and inclusivity in the literary world. Additionally, translation fosters cross-cultural dialogue and enriches the global literary landscape by introducing unique narrative styles and perspectives. Consequently, the translation of literary works plays a crucial role in shaping a more interconnected and culturally aware global society. Implications to Theory, Practice and Policy: Cultural translation theory, the polysystem theory and postcolonial translation theory may be used to anchor future studies on assessing the role of translation in global literary circulation. To enhance practical applications, stakeholders in the literary community should prioritize collaborative translation initiatives that involve diverse perspectives and expertise. In shaping policy frameworks, policymakers should prioritize funding initiatives that support translation projects for underrepresented literary traditions and genres.